Study of burst abdomen: it’s causes and management - Jaiswal, N. K.; Shekhar, Sandeep (International Surgery Journal, 2018)
Background: Burst abdomen (abdominal wound dehiscence) is a severe post-operative complication. Burst abdomen is defined as post-operative separation of abdominal musculo-aponeurotic layers. The study aims to find etiological factors of burst abdomen in hospitalised patients ,evaluate current management methods and to compare conservative and operative approach with respect to complication and outcomes. Methods: All cases presenting with abdominal wound dehiscence after surgery were included. An elaborate clinical history was taken in view of the significant risk factors, the types of surgery performed , type of disease involved and management methods and their outcome. A total of 82 cases were included in this prospective study. Data was analysed using appropriate software. Results: The results concluded that male patients have a higher incidence of laparotomy wound dehiscence and in 5th decade. Patients presenting with peritonitis secondary to gastro-duodenal perforation are more prone to burst abdomen. Conclusions: Burst abdomen is a serious sequel of impaired wound healing. Presence of anaemia, hypoproteinemia favours high incidence of burst abdomen. Delayed suturing, of burst abdomen has a lower frequency of complications . Adherence to proper technique and sincere efforts to minimize the impact of the predisposing factors play a much larger role in both treatment and prevention of this condition.